A Review Of Various Protection Schemes Of Power Transformers - et. al., Vijay Kumar Sahu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The power transformer is an electrical equipment that needs continuous monitoring and fast protection since it is very expensive and essential element for power system to perform effectively. Various methods for the protection are available. Most of the methods should be known for the protection of the transformer before practically protecting the same. Here a review is presented for various methods available for the protection of transformer. The most common protection technique used is the percentage differential logic, which provides discrimination between different operating conditions and internal fault. Some condition as, inrush current and CT saturation can cause mis-operation of differential protection. Few methods to solve this problem are also reviewed. Dissolved gas analysis (DGA) of power transformer is an investigative tool to monitor its health and to detect failures by recognizing anomalous patterns of DGA concentrations is also discussed. Some additional methods for transformer protection are also reviewed, as thermography method. Finally, a conclusion on different methods available for better performance is presented.